A Study of the Influence of Economic Factors on World Silver Production - KUBESA, Jiří; ČERNÝ, Igor (GeoScience Engineering, 2023)
Silver is a very important raw material used in industry, especially in the electrical and energy industries. With the increase in electromobility, its potential will grow in the future, and any shortage of silver on the world market could be a threat to modern industry. This article deals with the influence of economic factors (price, population, gross domestic product (GDP) and cumulative inflation) on silver production and the creation of appropriate econometric models that best express the relationship between production and economic factors for the period 2000–2020. The influence of economic factors on world silver production is examined using the coefficient of determination and information criteria. The authors use regression analysis in the article, especially these four types: linear, exponential, logarithmic and power. It is evident from the research that the best functional form of regression is exponential according to the coefficient of determination. Based on the investigated economic factors, it has been found that the price is unsuitable for the creation of econometrics; on the other hand, the other factors are eligible. Keywords: Coefficient of determination; Econometric model; Economic factors; Information criteria; World silver production.